Pengaruh Electronic Word Of Mouth Dan Persepsi Harga Terhadap Keputusan Pembelian Dalam Membeli Seblak Di Daerah Tirtayasa - Badriyah Badriyah; Sukiyah Sukiyah; Siti Mariskah; Riki Gana Suyatna (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study is motivated by the competition of seblak business actors in the Tirtayasa area. This study aims to determine how influential the Electronic Word of Mouth variable is on price perceptions, on purchasing decisions. The population in this study were all buyers who bought Seblak in the Tirtayasa area. The research methodology used quantitative with respondents in this study were the Tirtayasa community, 64 community respondents who had bought Seblak Tirtayasa were obtained. Then the data was obtained using a questionnaire. The results showed that Electronic Word of Mouth (X1) 57.8% has a significant effect on purchasing decisions (Y) 73.4% price perception (X2) 57.8% has a significant effect on purchasing decisions (Y).